2012
DOI: 10.4048/jbc.2012.15.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Techniques for Personalized Oncoplastic Surgery in Breast Cancer Patients with Small- to Moderate-Sized Breasts (Part 1): Volume Displacement

Abstract: Despite the popularity of breast-conserving surgery (BCS), which constitutes 50-60% of all breast cancer surgeries, discussions regarding cosmetic results after BCS are not specifically conducted. The simple conservation of breast tissue is no longer adequate to qualify for BCS completion. The incorporation of oncological and plastic surgery techniques allows for the complete resection of local disease while achieving superior cosmetic outcome. Oncoplastic BCS can be performed in one of the following two ways:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 8 publications
(12 reference statements)
1
38
0
Order By: Relevance
“…It represents the major advance in the conservative treatment of breast cancer in the last decades 3 . Studies have shown a higher satisfaction rate with aesthetic result when using oncoplastic techniques, indenpendently of the extent of resected breast volume tissue 12 .…”
Section: Discussionmentioning
confidence: 99%
“…It represents the major advance in the conservative treatment of breast cancer in the last decades 3 . Studies have shown a higher satisfaction rate with aesthetic result when using oncoplastic techniques, indenpendently of the extent of resected breast volume tissue 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative Approach; It has been reported that OBS does not influence the selection and timing of postoperative adjuvant therapy (41,70,71). It was demonstrated that complications in patients with oncoplastic reduction or volume expansion did not delay adjuvant treatment (70,71,72).…”
Section: Oncologic and Esthetic Evaluationmentioning
confidence: 99%
“…It was demonstrated that complications in patients with oncoplastic reduction or volume expansion did not delay adjuvant treatment (70,71,72). In a similar group of patients, there are publications stating that serious complications such as flap nutritional problems resulted in a few weeks of delay in adjuvant treatment (55,73).…”
Section: Oncologic and Esthetic Evaluationmentioning
confidence: 99%
“…Nevertheless, oncoplastic techniques that have evolved in the past decade are increasingly being incorporated into WLE to allow more extensive resections and to achieve a superior cosmetic outcome. 6,7 Such techniques can involve extensive mobilization of the breast plates to reshape the breast, and can even involve volume replacement with autologous tissue flaps, and are often not suitable as ambulatory procedures. Newer modalities, such as intraoperative radiotherapy following WLE for low-risk cancers, however, have been associated with minimal morbidity and do not compromise the suitability for ambulatory surgery.…”
Section: Introductionmentioning
confidence: 99%